PENERAPAN MODEL PBL BERBANTUAN MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS I DI SDN SUKORAME 2 - Ilmawati Fahmi Imron; Nurul Mubarokah; Afandi, Sekar Kinayafadia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on the results of learning mathematics of class I SDN Sukorame 2, in essence, non-standard units of length, 3 out of 28 students did not meet the Minimum Mastery Criteria (KKM) of 75 points. This study aims to develop mathematics learning outcomes by using question cards together with the Problem-Based Learning (PBL) strategy. Question cards and the PBL approach are expected to meet students' learning needs and improve their academic achievement. The use of the PTK methodology in the study, which has been carried out for two cycles and is based on the modified Kemmis and McTaggart model. The preparation, implementation, observation, and reflection stages are all included in each cycle. According to the research findings, the average score of students increased significantly from 70 in the pre-cycle to 74 in the first cycle and then to 89 in the second cycle. This shows how the PBL paradigm has succeeded in improving mathematics learning outcomes for first-grade students of SDN Sukorame 2 when used with question card material.